Carl Schmitt, un marcionite moderne ? - Storme, Tristan (Revue des sciences philosophiques et théologiques, 2011)
Ever since the publication in French of Carl Schmitt’s Leviathan, the jurist’s anti-semitism has been, in France, at the centre of the debates surrounding the political theorist’s thinking. In this article, the author aims to approach the catholic thinker’s aversion to Judaism, by privileging a singular angle. Supporting itself on biblical phenomena and religious themes present in the German thinker’s writings, this article seeks to investigate the intuition that there exists an intellectual affinity between Schmitt and Marcion, an intuition overheard here and there but demanding thorough inquiry. To this end, the author articulates the hypothesis of a « theological-political » Marcionism that he then attempts to apply and test throughout the entire body of Schmitt’s work. At stake is whether or not for the Catholic jurist, Judaism’s theologically political implications are radically incompatible with those of Christianity.